Providing Incentive Guarantees and Privileges for Health Services in the Implementation of Legal Protection for Health Workers During the Covid-19 Pandemic - Muhammad Aziz; Maftuh Maftuh; Bayu Mujrimin; Moh. Agus Sifa'; Sandro Wahyu Permadi (Fakultas Syariah, 2022)
Abstract: The research aims to explain the implementation of legal protection for health workers in Indonesia during the COVID-19 pandemic. Health workers are people who are engaged in the health sector to provide assistance to people who need healing of physical conditions. Indonesia is being hit by the Covid-19 outbreak which has killed many health workers in their work. At the same time, health workers are intimidated by people who are worried about the spread of the virus to their homes, so that health workers become victims of bullying by the community. The research method used is normative juridical with analytical prescriptive research specifications and is carried out with an analytical approach, a law approach, a literature approach, a concept approach, equipped with primary, secondary, and tertiary legal materials as data fulfillment in this study. This research concludes that the implementation of the protection of health workers in Indonesia is carried out through a policy of providing high incentive guarantees, privileges in health services, and special family insurance for health workers. Such a model for implementing the protection of health workers needs to be given, in order to guarantee legal protection and human rights in their duties to provide assistance to humanity and the safety of the nation in the context of treating and preventing the Covid-19 virus outbreak.Keywords: covid-19; worker; health.Abstrak:Riset bertujuan untuk menjelaskan pelaksanaan perlindungan hukum bagi tenaga Kesehatan di Indonesia selama pandemic covid-19. Tenaga kesehatan adalah orang yang bergerak di bidang kesehatan untuk memberikan bantuan kepada masyarakat yang membutuhkan penyembuhan kondisi fisik. Indonesia sedang dilanda wabah Covid-19 yang telah menewaskan banyak tenaga kesehatan dalam pekerjaannya. Pada saat yang sama, petugas kesehatan diintimidasi oleh orang yang khawatir terhadap penyebaran virus ke tempat tinggalnya, sehingga petugas kesehatan menjadi korban bullying oleh masyarakat. Metode penelitian yang digunakan adalah yuridis normatif dengan spesifikasi penelitian preskriptif analitis dan dilakukan dengan pendekatan analitik, pendekatan undang-undang, pendekatan literatur, pendekatan konsep, dilengkapi dengan bahan hukum primer, sekunder, dan tersier sebagai pemenuhan data dalam penelitian ini. Riset ini menyimpulkan, bahwa pelaksanaan perlindungan tenaga kesehatan di Indonesia dijalankan melalui sebuah kebijakan pemberian jaminan insentif yang tinggi, pengistimewaan dalam layanan kesehatan (dosis vaksis khusus), dan jaminan keluarga tenaga kesehatan yang istimewa (santuan kematian). Pelaksanaan perlindungan tenaga kesehatan semacam itu perlu diberikan, dalam rangka mendapatkan jaminan perlindungan hukum dan hak asasi manusia dalam tugasnya memberikan bantuan bagi kemanusiaan dan keselamatan bangsa dalam rangka pengobatan dan pencegahan wabah virus Covid-19.Kata kunci: covid-19; pekerja; Kesehatan.